The Implementation of the Guided Inquiry Model in Basic Chemistry Courses - Cyndi Prasetya; Maisarah Maisarah; Mulyani Mulyani (Journal of Educational Chemistry (JEC), 2023)
The study aimed to provide an overview of the application of the model in Basic Chemistry learning and its impact on student abilities. The researchers employed a descriptive qualitative method, focusing on the Guided Inquiry Model applied in Basic Chemistry courses. The primary data source was documentation, administering the data collection technique in the form of documentation analysis involving photos of the Guided Inquiry Model activities. The findings revealed two key points: Firstly, there was an improvement in students' knowledge and insights about basic chemistry, such as recognizing that the purification of substances could effectively separate naphthalene from its contaminants. Secondly, the implementation of the Guided Inquiry Model in Basic Chemistry courses involved four stages. The process began with problem orientation, framed by the question: "When naphthalene is contaminated, how can it be separated from its pollutants?" The subsequent stage involved formulating a hypothesis through discussions, culminating in an agreed-upon alternative hypothesis: “The practice of purifying substances can successfully separate naphthalene from its contaminants.” In the exploratory stage, students engaged in practical purification activities guided by the practicum guidebook and lecturer instructions. The final stage encompassed formulating generalizations, concluding that purifying substances through sublimation could effectively separate naphthalene from pollutants. As a recommendation, this study suggested that lecturers adopt the Guided Inquiry Model because it could enhance students' understanding of the materials covered in Basic Chemistry courses.